Eksistensi dan Fungsi Sosial Ritual Ratib Samman pada Masyarakat Desa Sei Paham Kecamatan Sei Kepayang Kabupaten Asahan - Siregar, Saidatul Ulya; Ritonga, Sakti; Ismail, Ismail (Asian Journal of Islamic Studies and Da'wah, 2023)
This study aims to determine the exixtence, practice, meaning and social function of the Ratib Samman ritual in the people of Sei Paham Village, Sei Kepayang District, Asahan Regency. The ritual which is carried out by gathering many people is carried out by men at night after the Isha Prayer. This study uses a qualitative method with a descriptive approach. In this case, to obtain the data inquestion, obtained trough observation, interviews and documentation. The results of this study indicate that the existence of the Ratib Samman ritual is a cultural form that is believed and known by the community to have existed from the time of the Atok ancestors and was passed down from generation to generation. Its existence has a high value in society, the practice starts from the pre-implementation stage, the implementation stage and the post-implementation stage. The movements used are sitting, rotating and standing positions as well as the movements of the pencak silat moves. The community interprets this ritual as the practice of remembrace of Allah Swt to draw closer Allah Swt. It is known that these rituals are part of the teaching of the Tarekat. Howefer, in this area, it has become a public Ratib, meaning that anyone may follow it. The ritual also has a social function, among others, as a form of social solidarity an integration and as a means of overcoming epidemics or diseases, famine, crime, and disturbances by spirits.